1994
DOI: 10.1073/pnas.91.16.7583
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and cGMP cause vasorelaxation by activation of a charybdotoxin-sensitive K channel by cGMP-dependent protein kinase.

Abstract: Nitric oxide (NO)-induced relaxation is assodated with increased levels ofcGMP in vascular smooth muscle cells. However, the mechanism by which cGMP causes relaxation is unknown. This study tested the hypothesis that activation of Ca-sensitive K (Kc.) chanels, mediated by a cGMPdependent protein kinase, is responsible for the relaxation occurring in response to cGMP. In rat pulmonary artery rings, cGMP-dependent, but not cGMP-independent, relaxation was inhibited by tetraethylammonium, a classical K-channel bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
458
1
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 731 publications
(480 citation statements)
references
References 29 publications
(30 reference statements)
15
458
1
6
Order By: Relevance
“…Because TEA blocks most K ϩ channels under the conditions employed, it appears that the NO donor SNAP does not induce a cGMP-independent relaxation through the activation of K ϩ channels in BPA. The role for NO in opening K ϩ channels via a cGMP mechanism may be an important part of smooth muscle relaxation in some systems (1), and evidence for the functional significance of this mechanism was detected in the present study when vascular segments were contracted with U-46619 under 21% O 2 . An increase in the level of membrane depolarization with 30 mM K ϩ and/or hypoxia (20) may have prevented the detection of cGMP-mediated relaxation in BPA through the opening of K ϩ channels under these conditions.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Because TEA blocks most K ϩ channels under the conditions employed, it appears that the NO donor SNAP does not induce a cGMP-independent relaxation through the activation of K ϩ channels in BPA. The role for NO in opening K ϩ channels via a cGMP mechanism may be an important part of smooth muscle relaxation in some systems (1), and evidence for the functional significance of this mechanism was detected in the present study when vascular segments were contracted with U-46619 under 21% O 2 . An increase in the level of membrane depolarization with 30 mM K ϩ and/or hypoxia (20) may have prevented the detection of cGMP-mediated relaxation in BPA through the opening of K ϩ channels under these conditions.…”
Section: Discussionsupporting
confidence: 69%
“…There is evidence that the opening of K ϩ channels in vascular smooth muscle is an important process involved in cGMP-dependent and cGMP-independent NO-mediated relaxation mechanisms (1,3). Thus the opening of K ϩ channels and the production of relaxation through hyperpolarization could potentially contribute to the mechanisms involved in NO-mediated relaxation under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that the ECH-induced relaxation was significantly weaker at the highest concentration of ECH in rings after treatment with TEA (1 mmol/L) compared with the control. NO-induced vasodilation is due in part to a cGMP-dependent, protein kinase G-mediated activation of BK Ca channels [24] . Therefore, we assumed that ECH induced rat pulmonary artery vasorelaxation via the NO-cGMP-PKG-BK Ca channels, which led to a decrease in intracellular Ca 2+ levels and the relaxation of PASMCs.…”
Section: Discussionmentioning
confidence: 99%